The TAB guide to vacuum tube audio : understanding and building tube amps - Whitaker, Jerry C. (New York : McGraw-Hill, 2012)
'Learn how to work with vacuum tubes and construct high-quality audio amplifiers on your workbench with help from this hands-on resource. The TABTM Guide to Vacuum Tube Audio: Understanding and Building Tube Amps explains tube theory and circuit analysis. Seven ready-to-build projects feature step-by-step instructions, detailed schematics, and layout tips. You'll also find out how to tweak the project designs and engineer your own custom-built, high-performance amps'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Amplifiers, Vacuum-tube.; TECHNOLOGY & ENGINEERING / Acoustics & Sound